1970
DOI: 10.5755/j01.ms.17.2.485
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Wear Behaviour of Sewn Assemblies of Viscose Linings with Different Treatment

Abstract: Different types of chemical treatment of textile are widely applied in advanced textile. Finishing of textile can provide additional functional properties for products or/and to improve the appearance of final product as well as to improve their mechanical properties. In this research the influence of the industrial treatment of viscose linings on the parameters of fabric surface friction, on fabric surface appearance as well as on the slippage resistance of yarns at a seam was investigated. Raw, dyed, dyed an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Research paper [8] of other authors illustrates that slippage of the seam formed by the sewing process is usually observed in fabrics containing higher floats of threads. Slippage of fabric threads at the seam may be defined by shifting of fabric threads due to the force applied.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Research paper [8] of other authors illustrates that slippage of the seam formed by the sewing process is usually observed in fabrics containing higher floats of threads. Slippage of fabric threads at the seam may be defined by shifting of fabric threads due to the force applied.…”
Section: Resultsmentioning
confidence: 96%
“…The aforesaid defect results from the force acting perpendicularly to the embroidered element direction. Textile weave and final finishing have been established to make influence on slippage of threads at the seam [8]. Within the stitch of the embroidered element, the textile is compressed and due to anisotropy, under the impact of certain forces, it gets deformed.…”
Section: Introduction *mentioning
confidence: 99%
“…The plain weave raw (z) lining fabrics with different industrial finishing (dyed (d), dyed and softened (d+m), dyed and treated with non-slip finishing (d+n)) [10] and the purposely weaved non stabilized fabrics: plain weave (D), twill weave (R) and combined twill weave (KR) were investigated in this research (Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…Some standard methods for the investigation of the yarn slippage at the sewn seams in the woven fabrics are known [8]. They are constantly developed, e. g. it is known, that application of standard method did not provide accurate results about the yarn slippage at the sewn seams in the lining woven fabrics and it was complemented with additional analysis of the captured images of the deformed sewn seams [9,10]. The other research works [11 -14] are committed to develop the more realistic imitation of clothing wearing conditions.…”
Section: Introduction *mentioning
confidence: 99%
“…Many studies [3 -6] shoved that the seam performance (seam strength, elongation, seam efficiency) depends on the interrelationship of fabrics, threads, the stitch and seam type selection and sewing conditions, which include the needle size, stitch density and etc. It was investigated [5] that type of fabric finishing improves wear behaviour (slippage resistance of yarns at a seam, friction) of sewn fabrics. In case of breathable waterproof fabrics, the seamed fabrics must be sealed with waterproof sealing tape to prevent water from penetration through the holes caused by stitching of needle.…”
Section: Introduction *mentioning
confidence: 99%